Kematangan emosi dalam perilaku ujaran kebencian pada kebijakan politik - Much. Faisal Abdul Afif; Yuni Nurhamidah; M. Fath Mashuri (Fakultas Psikologi, 2021)
The widespread use of social media by Indonesians has both positive and negative impacts. In addition, to making it easier for us to find information and reading sources, the use of social media also leaves negative impacts such as hate speech behavior that occurs on social media. One of the things that are thought to be correlated with hate speech behavior is emotional maturity. The purpose of this study was to determine the relationship between emotional maturity and hate speech behavior on social media towards political issues in Indonesia. The method used in this research is correlational quantitative, and using purposive sampling to select the subjects. Subjects of research were 205 person. In measuring the emotional maturity of this study using a Likert scale and hate speech behavior using a vignette scale. Data were analyzed using by the person product moment analysis technique. The results were that there was a negative relationship between the two variables with a significance value of<0.001 and a correlation coefficient value of -0.313, which means that the higher the emotional maturity of a person, the lower the level of hate speech behavior will be, and vice versa.